Pengaruh Kinerja Lingkungan dan Komponen Good Corporate Governance pada Nilai Perusahaan yang Terdaftar di BEI - Kurnia Uthami, I Gusti Ayu Agung Dewi; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi, 2018)
Corporate value is the condition achieved by the company as a form of trust from the community towards the company. Companies in their development and maximization should take into account their environmental responsibilities and corporate governance. The purpose of this research is to examine the effect of environmental performance and the componenets of good corporate governance on the corporate value. The sample in this research is 43 companies listed in the Indonesian Stock Exchange (IDX) and is selected using the purposive sampling method. Environmental performance is measured utilizing PROPER, while the components of good corporate governance are measured through managerial ownership, institutional ownership, audit committee and the board of independent commissionaires. Data collection is conducted using the documentation method. The data analysis technique utilized is the multiple linear regression analysis technique. The research result shows that managerial ownership, institutional ownership, and audit committee do not influence corporate value. While environmental performance and the board of independent commissionaires have a positive effect on the corporate value. Keywords :  environmental performance, good corporate governance, corporate value